Antibacterial activity and chemical characterization of almond (Prunus dulcis L.) peel extract. Issue 10 (19th May 2023) - Badalamenti, Natale; Bruno, Maurizio; Loizzo, Monica R.; Puccio, Valeria; Gaglio, Raimondo; Francesca, Nicola; Settanni, Luca; Sottile, Francesco
Abstract: In this study, almond skin of Prunus dulcis L. variety Casteltermini was characterised for its chemical composition and for the inhibitory activity towards food associated microorganisms belonging to pathogenic ( Salmonella Enteritidis, Staphylococcus aureus, Escherichia coli and Listeria monocytgenes ), spoilage ( Pseudomonas poae and Brochotrix thermospacta ) and useful ( Levilactobacillus brevis and Saccharomyces cerevisiae ) groups. The n -hexane extract of P. dulcis skin, investigated by GC–MS, evidenced linoleic, palmitic, and oleic acids as the main abundant compounds. Staphylococcus aureus ATCC 33862 growth was strongly limited by n -hexane extract and the minimum inhibition concentration (MIC) was 25.5 mg/mL. These results highlight the potential of almond by-products as food bio-preservatives as well as pharmaceutical products. Graphical Abstract: UF0001